Citrullus colocynthis (Bitter-apple): a comprehensive review on general properties, biological activities, phenolic and chemical contents - Mustafa SEVİNDİK; Imran UYSAL; Emre SEVINDIK; Tetiana KRUPODOROVA; Oğuzhan KOÇER; Orhan ÜNAL (Notulae Scientia Biologicae)
Plants display several biological activities as a result of the production of various chemicals inside their metabolic processes. In recent times, the growing prevalence of alternative medicine uses has elevated the significance of plants. The present work aimed to assess the biological activities, phenolic and chemical compositions, applicability, mineral composition, and overall characteristics of Citrullus colocynthis (L.) Schrad. as documented in existing literature. Literature study revealed that it possesses significant antioxidant, antibacterial, and anticancer properties. Furthermore, it has been observed that it may serve as a potential reservoir for the minerals documented inside its structure. It is also thought to be an important source, especially in terms of potassium. From this perspective, it became evident that the fruit components of the plant, in particular, could serve as a significant natural resource for promoting health.